Cardioprotective Effects of Luteolin on Ischemia/Reperfusion Injury in Diabetic Rats Are Modulated by eNOS and the Mitochondrial Permeability Transition Pathway. Issue 4 (April 2015) - Yang, Jin-Ting; Qian, Ling-Bo; Zhang, Feng-Jiang; Wang, Jue; Ai, Heng; Tang, Li-Hui; Wang, Hui-Ping
Abstract : Abstract: Myocardial ischemia/reperfusion (I/R) injury in diabetes is associated with oxidative stress, endothelial nitric oxide synthase (eNOS) dysfunction, and mitochondrial collapse, whereas luteolin is known to protect the cardiovascular system against diabetes and I/R injury. Here, we investigated whether luteolin pretreatment diminishes myocardial I/R injury in diabetic rats by affecting eNOS and the mitochondrial permeability transition pore (mPTP). After diabetic rats were produced by streptozotocin treatment (65 mg/kg) for 3 weeks, luteolin (100 mg·kg −1 ·d −1 ) or L-NAME (25 mg·kg −1 ·d −1 ) was administered intragastrically for 2 weeks. Hearts were then isolated and subjected to 30 minutes of global ischemia followed by 120 minutes of reperfusion. Pretreatment with luteolin significantly improved left ventricular function and coronary flow throughout reperfusion, increased cardiac tissue viability and manganese superoxide dismutase (MnSOD) activity, and reduced coronary lactate dehydrogenase release, and the myocardial malonaldehyde level in diabetic I/R rat hearts. All these improving effects of luteolin were significantly attenuated by L-NAME. Luteolin also significantly upregulated eNOS expression in diabetic rat hearts after I/R. Ca 2+ -induced mPTP opening and mitochondrial inner membrane potential reduction were significantly inhibited in ventricular myocytes isolated from luteolin-treated diabetic rats, and this effect was attenuated by L-NAME. These findings indicate that luteolin protects the diabetic heart against I/R injury by upregulating the myocardial eNOS pathway, and downstream effects include the enhancement of MnSOD and inhibition of mPTP.